Dietary supplementation of Lactobacillus zeae regulated the gut microbiome in piglets infected with enterotoxigenic Escherichia coli - Qian Zhang; Lijuan Zhang; Yang Lyu; Yutao Shi; Liangyun Zhu; Min Zhang; Yuyan Zhao; Di Zhao; Lei Wang; Dan Yi; Yongqing Hou; Tao Wu (Czech Journal of Animal Science, 2022)
This study was conducted to investigate the effect of Lactobacillus zeae LB2 on the gut microbiota in piglets infected with enterotoxigenic Escherichia coli (ETEC). Thirty-two healthy 7-day-old piglets were randomly divided into four treatment groups: control group (basal diet), LB2 group (supplemented with 1 × 108 CFU/pig/day L. zeae LB2), ETEC group (infected with 1 × 1010 CFU/pig/day ETEC) and ETEC+LB2 group (LB2 supplementation + ETEC infection). Intestinal contents were collected for DNA extraction and Illumina sequencing. Significant result was observed for alpha diversity in the four intestinal sections, and both ETEC infection and LB2 supplementation showed a higher Chao1 alpha diversity. At the phylum level, Firmicutes and Bacteroidetes were dominant in the healthy piglets, while Proteobacteria were dominant in the ETEC-infected piglets. At the genus level, ETEC infection decreased the abundance of Prevotella, Ruminococcaceae, Lactobacillus, Alloprevotella, Flavobacterium, and Sutterella and increased the abundance of Actinobacillus. The LB2 supplementation reduced the abundance of Ruminococcaceae, Actinobacillus, Porphyromonas, and Alloprevotella, and increased the abundance of Prevotella and Lactobacillus. Both ETEC infection and LB2 supplementation affected several functional pathways associated with cellular processes, environmental information processing, genetic information processing, diseases, metabolism, and organismal systems. In summary, ETEC infection induced dysbiosis of the gut microbiome in piglets, while L. zeae supplementation could positively regulate the gut microbiome during ETEC infection. Therefore, L. zeae LB2 may be an ideal probiotic for the prevention or treatment of ETEC infection.